Women’s control over income and household spending decisions: A rapid review - Eissler, Sarah; Bryan, Elizabeth (International Food Policy Research Institute, 2025)
Often-cited studies show that when women influence or control household spending decisions, they tend to spend in ways that improve the welfare of their household. However, these studies are decades old, and the most recent review of this evidence was published over a decade ago (see Doss 2013). We present a rapid review of this literature since 2013 on women’s relative bargaining power over household resource allocation and its relationship with key well-being outcomes. Specifically, we review the evidence to answer the following questions: 1) Does women’s control over income within the household influence household expenditure patterns?; 2) Does the source of women’s income matter for spending decisions?; and 3) Does the amount of women’s income matter for spending decisions?